Analisis Pengaruh Komitmen Organisasional dan Ketidakpastian Lingkungan terhadap Hubungan antara Partisipasi Anggaran dengan Senjangan Anggaran - Edfan Darlis (The Indonesian Journal of Accounting Research, 2013)
The issue of whether budget participation reduces slack has attracted the interest of many researchers. However, as indicated by Nouri and Parker (1996), studies examining the impact of participation on slack has not produced consistent results. Several studies found that participation reduced budget lack, while others found that participation increased budget slack.Adopting a contingency approach, this study argues that the effect of participation on budget slack is affected by other factors. In particular, this study examined the extent to which organizational commitment and environmental uncertainty moderated the relationship between participation and slack. It is hypothesized that, first participation reduces performance for individuals with high performance, and vice verse. Second, in situation of high uncertainty, participation reduces slack, but in situation of low uncertainty, participation increases slack.Base on responses of 54 managers, the results show that emotions attachment, a dimension of organizational commitment, moderated the relationship between participation and slack.